The effect of polyamines on the binding of anti-DNA antibodies from patients with SLE and normal human subjects - Wang, Xiao; Stearns, Nancy A.; Li, Xingfu; Pisetsky, David S. (Clinical immunology (Orlando, Fla.), 2014)
Antibodies to DNA (anti-DNA) are the serological hallmark of systemic lupus erythematosus (SLE). To elucidate specificity further, the effect of polyamines on the binding of anti-DNA antibodies from patients with lupus was tested by ELISA to calf thymus (CT) DNA; we also assessed the binding of plasmas of patients and normal human subjects (NHS) to Micrococcus luteus (MC) DNA. As these studies showed, spermine can dose-dependently inhibit SLE anti-DNA binding to CT DNA and can promote dissociation of preformed immune complexes. With MC DNA as antigen, spermine failed to inhibit the NHS anti-DNA binding. Studies using plasmas adsorbed to a CT DNA cellulose affinity indicated that SLE plasmas are mixtures of anti-DNA that differ in inhibition by spermine and binding to conserved and non-conserved determinants. Together, these studies demonstrate that spermine can influence the binding of anti-DNA autoantibodies and may contribute to the antigenicity of DNA. •Spermine can inhibit the binding of lupus anti-DNA to mammalian DNA.•Spermine does not affect selective anti-DNA binding to bacterial DNA.•Lupus plasmas contain mixtures of anti-DNA differing in inhibition by spermine.•The antigenic determinants bound by anti-DNA in normal and lupus plasma differ.•Spermine may influence the properties of DNA as an autoantigen.